Frequency-Driven Crack Propagation in Ultrasonically-Assisted Bone Cutting - Qianrui, Du; Kamaludin, Sarah; Yusoff, Norwahida (International Journal of Integrated Engineering, 2022)
Ultrasonically-assisted bone cutting with high precision has many advantages for orthopedic surgeries. However, irregular crack propagation, large fractured chips, and surface damage may occur during the cutting process due to the brittleness and anisotropy of cortical bone. These can be minimized by optimizing the operating parameters of the cutting tool; cutting frequency, amplitude, speed, depth, and temperature, in consideration of the toughening mechanism of bone. Therefore, the current study is motivated to investigate the effect of varying frequency on crack propagation in ultrasonically-assisted bone cutting through the means of finite element analysis. The pattern of crack propagation in relation to the variation of frequencies was investigated using the extended finite element method (XFEM) in consideration of the bone microstructures. The results showed that crack propagation is effectively controlled when the tool is operated at higher frequencies, but an up-forward crack propagation following the trajectory of tool vibration is only apparent at frequencies higher than 800 Hz. Neglecting the operating outputs at 2400 Hz, the induced force and stress are observed to decrease proportionally with increasing frequency.